Analisis Intensi Berprestasi Mahasiswa Binus Online Learning - Putranto, Agus; Saputra, Wawan (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The utilization of e-learning can improve learning effectiveness and flexibility. Universitas Bina Nusantara (BINUS) provides an online learning program called BINUS Online learning. It offers the student to do a study through online activities, where the students are couraged to learn individually. This research was conducted to obtain a perspective of student intention from BINUS Online learning to mark good achievement. Non experimental method with quatitative approached is implemented where the respondents are students of Information System department and Marketing Management Department. The sampling techniques used is non probability purposive sampling. All variables are measured using questionnaire based on Fishbein and Ajzen model. The data of the research are analyzed using descriptive statistics and multiple linier regression analysis. The results show that the intention to mark an achievement of students of BINUS Online learning is very high. It means that BINUS Online learning Program students have strong intention to get good marks and study achievements.